Fa'āliyat Wasāith al-Ta'līm bi Qā'imat al Sam'ī 'ala Mustawa al Mutawasithah li al Mawādi al Kitabah - Nur Aini Puji Mastutik; Junaedi Junaedi (Thariqah Ilmiah: Jurnal ilmu-ilmu kependidikan dan Bahasa Arab, 2022)
The effectiveness of audiovisual learning media at the intermediate level for writing subjects The purpose of this research is to reveal the effectiveness of audio media in learning the material of the kitabah and find out the advantages and disadvantages of using the media. The method in this research uses descriptive qualitative with a field study approach. While for the research technique, the researcher used observation and documentation techniques.  And the sample of this study is the mutawassitah level students at the Raudlah al-Lughah al-Arabiyah Islamic boarding school Annuqayah Guluk-Guluk Madura. Researcher used qualitative method because researcher considered it would be easier to generate data or information. For the research approach, researcher need a field study approach to determine the validity of the data or information obtained. The result obtained in the study is the use of audio media in the kitabah material is considered to be effective. This effectiveness does not miss from the advantages and the disadvantages. One of the advantages of using audio media in learning is the acquisition of various kinds of knowledge in accordance with the application of audio in learning. While the advantages in the material delivered through the audio, which is not using the material delivered by native Arabs.